Exercise Loading Strategies for Patellar Tendinopathy: A Systematic Review and Meta-Analysis of Clinical Outcomes - Alejandro Bruna-Mejias; Rodrigo Cañas-Jamett; Juan José Valenzuela Fuenzalida; María P. Daza-Moya; Gustavo Oyanedel; Gloria Cifuentes-Suazo; Lorena Villaroel; Mathias Orellana Donoso; Eduardo Mateluna-Valls; Juan Jose Cabeza-Salgado; José E. León-Rojas; Juan Sanchis-Gimeno (Journal of Functional Morphology and Kinesiology, 2026)
Background: Patellar tendinopathy is a persistent load-related condition in athletes, and exercise is recommended as first-line care; however, the comparative value of specific tendon-loading prescriptions remains uncertain. This systematic review aimed to synthesize exercise-based interventions for adults with patellar tendinopathy, map reported loading prescription parameters, and estimate comparative effects when sufficiently comparable active-loading data were available. Methods: We conducted a PROSPERO-registered systematic review following PRISMA 2020. MEDLINE/PubMed, Web of Science Core Collection, Scopus, SPORTDiscus, and CENTRAL via Ovid/EBMR Reviews were searched. Two reviewers independently screened studies, extracted data, and assessed risk of bias. The primary outcome was VISA-P/VISA final score. Randomized active exercise/loading comparisons with extractable final-score data were pooled as mean differences on the original 0–100 scale using random-effects restricted maximum likelihood models with Hartung–Knapp adjustment. Results: The searches identified 942 records; 96 full-text reports were assessed and 40 reports were retained for qualitative synthesis. Six active exercise/loading comparisons contributed to the primary comparative synthesis. The pooled mean difference was 5.16 VISA-P/VISA points (95% CI 2.39 to 7.93) in favour of the first-listed intervention, with negligible statistical heterogeneity (tau2 = 0.000; I2 = 0.0%; Q = 3.50, p = 0.624). All contributing studies had some concerns in RoB 2, and GRADE certainty was low. Conclusions: Structured tendon-loading exercise remains central to rehabilitation. The pooled estimate should be interpreted as a small average comparative signal across clinically distinct active-loading contrasts, not as evidence that one specific loading strategy is universally superior.